First occurrences of Ni-phosphides in chromitites from the ophiolite complexes of Alapaevsk, Russia and Gerakini-Ormylia, Greece - Sideridis, Alkiviadis; Zaccarini, Federica; Grammatikopoulos, Tassos; Tsitsanis, Pavlos; Tsikouras, Basilios; Pushkarev, Evgeny; Garuti, Giorgio; Hatzipanagiotou, Konstantin (Ofioliti, 2018)
Small grains, approximately 15 μm in size, of a Ni-phosphide, have been discovered in two chromite deposits associated with altered mantle peridotite: (i) in Bakanov Kluch, Alapaesk ophiolite, Russia and (ii) in Agios Dimitrios, Gerakini-Ormylia ophiolite, Greece. On the basis of the chromite composition, both the Bakanov Kluch and the Agios Dimitrios chromitites are classified as Cr-rich chromitites with a boninitic affinity. Under reflected-light optical microscope, the Ni-phosphides are yellow in colour and isotropic. Their calculated stoichiometry, based on the average of 20 electron microprobe analyses, approaches the ideal formula (Ni,Fe)5P. One essential condition for the formation of terrestrial minerals in the Ni-Fe-P system is the presence of a highly reducing local geochemical environment. Serpentinization of oceanic peridotites produces reducing fluids containing dissolved H2 resulting from the reduction of H2O. Therefore, we suggest that the (Ni,Fe)5P from the Alapaevsk and Gerakini-Ormylia were very likely formed after the precipitation of the host chromitites during the serpentinization process at low temperatures. Nickel may have been released during the alteration of olivine and phosphorous may represent an alteration product of apatite. The (Ni,Fe)5P grains analyzed in the present work contain the highest value of Ni and they are characterized by the highest Ni to P ratio reported so far from similar minerals. Their stoichiometry indicates that the (Ni,Fe)5P grains found in the Alapaevsk and Gerakini-Ormylia chromitites represent a new mineral species. However, their small size prevents the acquisition of crystallographic data to support this assumption.